Sustainable valorization of poultry by-products: Optimized extraction of gelatin from chicken feet using acid treatments - Afidah, Ulil; Intan, Sirly Eka Nur; Putri, Amaliya; Kushendrayani, Anisa; Pradana, Nikolaus Raka; Manusama, Karina; Tamimi, Masagus Haidir (Journal of Advanced Veterinary Research, 2025)
Chicken feet, a major by-product of poultry slaughterhouses, are underutilized despite their high collagen content, which can be converted into gelatin. This study aimed to optimize gelatin extraction from chicken feet using hydrochloric acid (HCl) and phosphoric acid through Response Surface Methodology (RSM), focusing on yield, pH, lightness (L*), and viscosity. Extraction conditions were varied by acid concentration and soaking duration. Results showed that prolonged extraction time significantly improved yield, while excessively high acid concentrations led to over-hydrolysis and reduced recovery. Optimized conditions for HCl were achieved at 2.09% concentration and 19.11 h soaking time with a yield of 8.45% (desirability 0.986), while phosphoric acid achieved optimal results at 11.06% and 21.51 h with a yield of 8.61% (desirability 1.00). Gelatin quality was strongly affected by pH, where near-neutral conditions enhanced structural stability. Lightness decreased with extended soaking, whereas viscosity was higher in phosphoric acid treatment compared to HCl. This research highlights the sustainable valorization of poultry by-products into value-added gelatin, supporting circular economy principles and offering an alternative source of functional biopolymer for food applications.